2020
DOI: 10.1155/2020/9210261
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hyperhomocysteinaemia and Associated Factors among Ethiopian Adult Population in a 2015 National Survey

Abstract: Hyperhomocysteinaemia (HHcy) is an independent risk factor for major cardiovascular diseases, but data on the prevalence and predictors of HHcy in low- and middle-income countries like Ethiopia are scant. The aim of this study was to estimate the prevalence of HHcy and associated risk factors in the Ethiopian adult population. A cross-sectional survey on risks of noncommunicable diseases (NCDs) using the STEPwise approach to surveillance (STEPS) survey was conducted between April and June 2015. A total of 4,17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The elderly may suffer from declined liver and kidney function due to insulted digestion and absorption in the process of Hcy metabolism [34]. In addition, high prevalence of HHcy among men might be due to more muscle mass, insufficient intake of fruits and vegetables resulting in low folic acid and vitamin content, and unhealthy lifestyle habits such as smoking, alcohol consumption, and lack of sleep [7,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly may suffer from declined liver and kidney function due to insulted digestion and absorption in the process of Hcy metabolism [34]. In addition, high prevalence of HHcy among men might be due to more muscle mass, insufficient intake of fruits and vegetables resulting in low folic acid and vitamin content, and unhealthy lifestyle habits such as smoking, alcohol consumption, and lack of sleep [7,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies investigated the prevalence of HHcy and its determinants to provide a scientific basis for an in-depth exploration of public health prevention strategies. According to epidemiological studies, the prevalence of HHcy varied substantially with demographic characteristics, geographical distributions, and years of investigation [7][8][9]. The determinants of HHcy include genetic defects of the enzymes involved in Hcy metabolism, nutritional deficiencies of vitamin cofactors, such as folate, vitamin B12 and B6 [10], coexisting diseases [9,11], environment, and lifestyle [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a study in Ethiopia and a study in Brazil, which found that low consumption of fruit and vegetable was major risk factors of hyperhomocysteinemia. 47 48 However, a number of studies shown that there is a close association between serum folate levels, VitB2 or VitB6 and plasma homocysteine concentrations. 43 49 And the consumption of fruits and vegetables is associated with an increase in serum folate and VitB levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HHcy was previously explored and found to vary geographically; however, more studies have focused on the associations between HHcy and specific diseases [ 5 , 6 , 8 , 13 ]. Different HHcy prevalences reported in different studies could be due to the various population inclusion criteria and different cutoff values adopted and may be affected by ethnicity, genetic factors, and lifestyle behaviors [ 14 , 15 ]. A meta-analysis by Yang and coworkers reported that the overall prevalence of HHcy in China was 27.5%, indicating that HHcy has become an important public health issue worthy of greater concern [ 16 ].…”
Section: Introductionmentioning
confidence: 99%